**x = 60**

**x = 10**

Not sure how to get the answer at all. I have the quadratic formula but I am not sure how to apply it

Tutors, sign in to answer this question.

Multiply both sides of the equation by -1. You get the following equation:

x^2 - 70x + 600 = 0

Factor the quadratic equation. You get:

(x - 60)(x - 10) = 0

x - 60 = 0

x - 10 = 0

Wael I. | Mathematics and Arabic LanguageMathematics and Arabic Language

Agree with Muhammad

you could also use the equation

x = (-b ± sqrt(b^{2}-4*a*c)/(2*a)

-x^2+70x-600

ax^2+bx+c

a = -1

b = 70

c = -600

x = (-b ± sqrt(b^2-4*a*c)/(2*a) = (-70 ± sqrt(70^2-4*(-1)*(-600))/(2*(-1))

x = (-70 ± sqrt(4900-2400)/(-2)

x = (-70 ± sqrt(2500)/(-2)

x = (-70 ± 50)/(-2)

x = (-70 + 50)/(-2) or x = (-70 - 50)/(-2)

x = (-20)/(-2) or x = (-120)/(-2)

x = 10 or x = 60

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.